Komunikasi Suara Sinyal Digital Dengan Transmisi Frekuensi 2,4 Ghz - Ahmad Wahyu Purwandi; Abdul Rasyid; Guntur Wahyu Sejati (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
The limitations of developing high-tech communication systems cause the area of people who can use this service to be uneven. One technology that can be used for areas not yet reached by this high-tech communication service is to use radio communication technology. Today radio communication technology continues to develop and produce an increasingly limited frequency spectrum. One way to improve the efficient use of available frequency spectrums is the transition from analog technology to digital technology. A very significant benefit in the use of digital technology is to save the use of radio frequency spectrum bandwidth with signal compression techniques. One device that still uses analog technology is a handy talky (HT). In addition to the lack of frequency spectrum efficiency, HT technology still requires a radio station license (ISR) for its use. This experiment designed a two-way digital audio communication system that was transmitted using the NRF24L01 radio frequency transceiver module on the 2.4Ghz frequency. Analog input data from the microphone will be converted into digital data through the ADC (Analog to Digital Converter) process using a microcontroller and the digital data that will be sent is first digitally modulated using GFSK modulation then transmitted digitally. On the other hand data that already contains voice information received again by another NRF24L01 transceiver is received by the Arduino microcontroller and then formed into a PWM signal (pulse width modulation) and then released to the speaker. So the method of using digital transmission can produce efficiencies in the frequency spectrum.